The elemental composition of leaves of promising species of decorative plants - K. S. Skrebtsova; Yu. A. Fedchenkova; O. P. Khvorost (Zaporozhye State Medical University, 2019)
The aim of the research is to determine the component composition of the mineral compounds of Crassula ovata leaves and Dieffenbachia Bowmannii leaves.Materials and methods. Raw materials - the leaves of Crassula ovata and Dieffenbachia Bowmannii were harvested from own grown plants during 2017. We used the method of atomic emission spectrography with photographic recording on a DFS-8 instrument to determine the composition of compounds of mineral nature.Results. It is established that the raw material - the leaves of the Crassula ovata and the leaves of Dieffenbachia Bowmannii have at least 19 elements. In the Crassula ovata leaves and Dieffenbachia Bowmannii leaves such macronutrients are accumulated in large quantities as: potassium - 2150 mg/100 g and 2580 mg/100 g, respectively, silicium 1120 mg/100 g and 1220 mg/100 g, respectively, and calcium - 900 mg/100 g and 1090 mg/100 g, respectively. The accumulation of elements in the leaves of Crassula ovata bollard is comparable to the accumulation of compounds of this group in the leaves of Dieffenbachia Bowmannii. Conclusions. The elemental composition of Crassula ovata leaves and Dieffenbachia Bowmannii leaves was studied by atomic emission spectrography with photographic recording. The presence of 19 elements has been established, of which in both types of raw materials dominate the content of potassium, silicium and calcium. The quantitative content of each of the elements in the leaves of Crassula ovata is comparable to the content in the leaves of Dieffenbachia Bowmannii